Adolescents with disability report higher rates of injury but lower rates of receiving care: findings from a national school-based survey in New Zealand. Issue 1 (30th June 2015) - Peiris-John, Roshini; Ameratunga, Shanthi; Lee, Arier; Al-Ani, Haya; Fleming, Theresa; Clark, Terryann
Abstract : Objective: This study investigates the associations between living with a disabling condition and experiencing clinically attended injuries, risk behaviours and difficulties accessing healthcare for injury among adolescents attending secondary (high) schools in New Zealand. Methods: A nationally representative cross-sectional self-report survey conducted in 2012 captured health and well-being data from 8500 secondary school students using a multimedia computer-assisted interview. Respondents reporting a disability or a long-term condition with functional limitations were defined as adolescents with a disabling condition (index group of interest). The association between experience of disability (or not) and injuries, related risk factors and access to healthcare was investigated using logistic regression models. Results: One in six students (n=1268, 14.9%) reported a disabling condition. Compared with their peers, these students had significantly increased odds of needing treatment in the previous 12 months for an injury related to an RTC (OR 1.53; 95% CI 1.11 to 2.10), fall (OR 1.30; 95% CI 1.08 to 1.57), near drowning (OR 2.50; 95% CI 1.40 to 4.48), assault (OR 2.13; 95% CI 1.50 to 3.02) and self-harm (OR 4.25; 95% CI 3.03 to 5.96). Students with disabilities were also at increased odds of reporting they had problems accessing healthcare for injury (OR 1.51; 95% CI 1.27 to 1.81). Adolescents with disability were more likely than their peers to have been a passenger in a vehicle where the driver was under the influence of drugs (OR 1.29; 95% CI 1.03 to 1.62) or was driving dangerously (OR 1.40; 95% CI 1.21 to 1.62). Conclusions: Acknowledging the likely underestimation of effects in a mainstream school survey, adolescents with disability face elevated odds of injury and yet have poorer access to healthcare. Environmental and systemic causes of these disparities require greater attention with implementation of effective interventions.